Work-in-progress on a thin IEEE1451.0 - architecture to implement reconfigurable Weblab infrastructures - Guedes, Ricardo J. (2014)
Institutions have been creating their own specific weblab infrastructures. Usually, they use distinct software and hardware architectures comprehending instruments and modules (I&M) able to be parameterized but difficult to be shared. These aspects are impairing their widespread in education, since collaboration between institutions, in developing and sharing resources, is still low. To handle both aspects, this paper proposes the adoption of the IEEE1451.0 Std. with FPGA technology for creating reconfigurable weblab infrastructures. It is suggested the adoption of an IEEE1451.0 infrastructure with compatible instruments, described in Hardware Description Languages (HDL), to be reconfigured in FPGA-based boards. Besides an overview of the IEEE1451.0 Std., this paper presents a solution currently under development which seeks to enable the reconfiguration and the remote control of weblab infrastructures using a set of IEEE1451.0 HTTP commands.